2004
DOI: 10.1097/01.icl.0000140228.24461.1b
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Reduction Using Corneal Refractive Therapy Contact Lenses

Abstract: The CRT lens is an effective modality for temporary myopic correction for a restricted subset of myopic candidates. Those with a spherical manifest refraction between -1.00 and -6.00 D and up to 1.50 D of astigmatism can expect a good outcome with these lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 3 publications
3
7
0
2
Order By: Relevance
“…[23][24][25]31 The slitlamp findings in this investigation are similar to those reported by others in short-term investigations in which most subjects have no positive slitlamp findings. [23][24][25][26] However, Rah et al 31 reported corneal staining after 1 month of overnight lens wear in approximately 80% at a morning visit followed by a 30% reduction at the afternoon visit on the same day. Of all the positive findings reported so far, superficial corneal staining has been the most prevalent positive finding.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[23][24][25]31 The slitlamp findings in this investigation are similar to those reported by others in short-term investigations in which most subjects have no positive slitlamp findings. [23][24][25][26] However, Rah et al 31 reported corneal staining after 1 month of overnight lens wear in approximately 80% at a morning visit followed by a 30% reduction at the afternoon visit on the same day. Of all the positive findings reported so far, superficial corneal staining has been the most prevalent positive finding.…”
Section: Discussionsupporting
confidence: 91%
“…Of all the positive findings reported so far, superficial corneal staining has been the most prevalent positive finding. The data from this investigation support Soni et al 23 and indicate a decrease in intensity and incidence with time. However, an increase in corneal neovascularization up to 3 months with stabilization in the following months is not consistent with the findings of Soni et al, 23 who reported no change in neovascularization after overnight wear in their 3-month investigation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In myopic patients with astigmatism, standard spherical orthokeratology does not consistently change the amount of astigmatism. Some studies have reported that orthokeratology causes significant changes in astigmatism while others have found no significant change in astigmatism …”
Section: Optical Changes With Myopic Orthokeratologymentioning
confidence: 99%